The reproductive health indices and sex hormone levels in middle-aged and elderly Chinese men. (2nd July 2016) - Li, Jian-Hui; Yu, Xiao-Hua; Zheng, Jun-Biao; Zhao, Jing; Wang, Jun; Shen, Yu-Zhong; Li, Yu-Min; Yu, Jin-Feng; Li, Dong; Xu, Jia-Neng; Zhu, Qian-Xi
Abstract: Objective : The aim of this study was to analyze the age-related recession trajectory of reproductive health indices in middle-aged and elderly Chinese men. Methods : A population-based cross-sectional study was conducted in Jiashan County, Zhejiang in 2012. Healthy men between 40 and 80 years of age were considered eligible for the study. Physical examination and the sex hormones were measured. The subjects were assessed based on the 5-item version of the International Index of Erectile Function (IIEF-5) for Erectile Dysfunction (ED), and Aging Males' Symptoms (AMS) scale for Symptomatic Late-Onset Hypogonadism (SLOH). Results : TG showed a decrease at age 60 years. Testis volume and TT did not show significant difference among the four age groups; cFT began to decrease at age 50 years and Bio-T decreased faster at age 50 years. SHBG and LH increased faster at age 50 and 70 years, respectively. IIEF5 score decrease faster at age 60 years. AMS scores increased faster at age 70 years. With the increase in age, the symptoms of ED and SLOH became severer. Conclusion : Different indices on reproductive health of men showed turning points at different ages. At first, androgenic sex hormones decreased faster, and then erectile dysfunction got severer, and the last overall male syndromes declined.